Intergovernmental Fiscal Relations and Grassroots Development in Nigeria: A Thematic Content Analysis of the State Joint Local Government Account (2000–2024) - Isaac Emoghene; Temitope Oluyemi (Universitas Medan Area, 2025)
Nigeria’s intergovernmental fiscal framework, particularly the State Joint Local Government Account (SJLGA), has long been criticised for undermining local autonomy and impeding grassroots development. This study examines how the SJLGA affects the fiscal independence and service delivery capacity of local governments. Drawing on thematic content analysis of scholarly articles, constitutional documents, audit reports, and empirical studies published between 2000 and 2024, the research identifies core themes shaping local governance outcomes. Findings reveal that the SJLGA fosters financial dependency, enabling state governments to control local allocations and impose political influence, often through caretaker committees. This centralisation reduces transparency, encourages resource misallocation, and leads to elite capture, where funds serve political interests rather than local development priorities. The analysis further shows that constitutional ambiguities and weak institutional safeguards exacerbate these problems, leaving local governments unable to fulfil essential mandates in education, healthcare, and infrastructure. The study argues that these systemic constraints contradict the principles of fiscal federalism and Local Government Theory, which advocate for subsidiarity and citizen-focused governance. To reverse these trends, it recommends constitutional reform to guarantee direct statutory transfers to local governments, the creation of independent oversight mechanisms, and strengthened democratic safeguards to ensure accountability. By highlighting the disconnect between constitutional intent and practical outcomes, this research underscores the urgent need to realign Nigeria’s fiscal architecture to empower local governments as true drivers of grassroots development and democratic accountability.